Investigation of nitroxide-mediated thermal and photochemical reactions of living free radical polymerization. - Skene, William G. (University of Ottawa (Canada), 2002)
The work presented in this thesis deals primarily with living free radical polymerization (LFRP). Two main specific areas of this process have been studied; thermal and photochemical reaction sequences. Stoichiometric unimolecular initiators were found to be ideal probes for studying the reactions involved in the LFRP process. The bond dissociation energy (BDE) of the labile C-O bond of the alkoxyamine initiators was found to be ca. 28 kcal/mol and is dependent on the resulting carbon centered radical produced upon thermal decomposition. Lower activation energies were measured for more stable carbon centered radicals. Complementary to the thermal studies, photoacoustic studies (PAC) involving photochemical decomposition of the initiators led to the homolytic N-O and C-O bond cleavages in addition to disproportionation product formation. The BDE for the N-O bond of these initiators is ca. 43 kcal/mol. These studies also provided insight into volume effects, where a strict homologous solvent series is not required for extrapolating true enthalpies of reactions and volume correction factors for PAC. The decomposition quantum yields of a series of ketone based actinometers used for PAC BDE studies were re-evaluated and found to be solvent independent. The specific kinetics of thermal LFRP were equally investigated through the use of probes which are normally used for thermal initiation. Fast time resolved techniques of laser flash photolysis (LFP) were used to measure the bi-molecular rate constant for the coupling reaction between a carbon centered radical and a nitroxide radical involved in LFRP. Typical values lay in the area of 108 M-1 s-1 and are influenced by the structure of the carbon centered radical and not that of the nitroxide. The rate constants were observed to be slower with more stable carbon centered radicals, similar to the BDE results where weaker dissociation energies were observed. The formation of minor disproportionation products upon thermal decomposition of the unimolecular initiators was assigned to a concerted four center elimination ultimately responsible for the lack of controlled polymerization with acrylates. The incorporation of steric effects into the monomer or the nitroxide suppressed the formation of these products by increasing the energy barrier necessary for correct orbital alignment required for the elimination reaction. Living polymerization of acrylate monomers was achieved with a nitroxide containing bulky substituents in its 2 and 6 positions. Moderate success of living polymerization was also achieved with acrylate type monomers through the use of an additional phase not miscible with the bulk phase. Chromophores producing triplet states upon excitation were found to undergo fast and efficient energy transfer to a covalently linked alkoxyamine subsequently promoting C-O bond homolysis. The orientation of the C-O bond relative to the chromophore in addition to the distance separating the two influences the efficiency of energy transfer and bond cleavage. Using a benzophenone type chromophore with a covalently linked alkoxyamine initiator promoted photoinduced living type polymerization of acrylate.
Keywords: Chemistry, Polymer.